Bactericidal activity of caprylic acid entrapped in mesoporous silica nanoparticles. (October 2015) - Ruiz-Rico, María; Fuentes, Cristina; Pérez-Esteve, Édgar; Jiménez-Belenguer, Ana I.; Quiles, Amparo; Marcos, María D.; Martínez-Máñez, Ramón; Barat, José M.
Abstract: Development of nanotechnologies to improve the functionality of natural antimicrobials for food applications has received much attention in recent years. Mesoporous silica particles, such as MCM-41, have been recently proposed as smart delivery devices capable of loading and releasing large amounts of cargo. In this study, the antimicrobial activity of caprylic acid entrapped in MCM-41 nanoparticles against Escherichia coli, Salmonella enterica, Staphylococcus aureus and Listeria monocytogenes was tested and compared with the bactericidal effect of free caprylic acid using the macrodilution method. The minimum bactericidal concentration for free caprylic acid was established to be below 18.5 mM for S. aureus and L. monocytogenes and within the 18.5–20 mM range for E. coli and S. enterica . Moreover, caprylic acid – loaded nanoparticles showed a total inhibition of the growth within the 18.5–20 mM range for the tested bacteria, and therefore the antimicrobial activity was preserved. Transmission electron microscopy images revealed that bacteria treatment with the caprylic acid-loaded nanoparticles generated disruption of cell envelope and leakage of cytoplasmic content, which resulted in cell death. We believe that caprylic acid encapsulation in nanoparticles MCM-41 can provide an effective system for potential applications in food safety in the food industry due to the possible controlled release of fatty acid and the masking of its unpleasant organoleptic properties. Highlights: A new antimicrobial system based on encapsulation of caprylic acid (CA) was developed. CA-loaded nanoparticles showed total inhibition of growth within the 18.5–20 mM range. The mode of action of CA was explained by TEM observations. CA-loaded nanoparticles generated disruption of cell envelope and cell death.